2002
DOI: 10.1111/0165-0203.00022
|View full text |Cite
|
Sign up to set email alerts
|

Transforming time into money using water: A participatory study of economics and gender in rural India

Abstract: When water supply improvements are coupled with opportunity to create income through micro-enterprises, time released from water collection is converted into income earned. This brings several benefits: reduced drudgery, higher household income, and, consequently, greater women's empowerment through changing gender relations within the household. This article documents the performance of one such scheme in Banaskantha District in the state of Gujarat in India, one of poorest districts in the state and the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Control by others of one's time is unlikely to lead to full control over achieving own goals. In their study in rural India, James et al (2002), showed how women participants' increased control over own time enhanced their empowerment because women decided to get involved in revenue-generating activities that strengthened their intra-household decision-making and status.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…Control by others of one's time is unlikely to lead to full control over achieving own goals. In their study in rural India, James et al (2002), showed how women participants' increased control over own time enhanced their empowerment because women decided to get involved in revenue-generating activities that strengthened their intra-household decision-making and status.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…An additional programme of support for the women to develop handicrafts addressed the usual constraints to taking up new enterprises-lack of funds and poor access to credit. 40 Clearly, time saved in water carrying does not generally result in women being less productive. 12 Only the nature of the tasks change.…”
Section: Releasing Time To Earn An Incomementioning
confidence: 99%
“…In addition, similarly to other countries, poor WSS mostly affects the most vulnerable. Water fetching in India is essentially a task for women and children, with according to some estimates three times as many women as men fetching water (James et al (2002)). In terms of health burden, diarrhea claims 10% of all deaths amongst women, compared to 7% of men in -2003in India (Office of Registrar General, 2004.…”
Section: Water Supply and Sanitation In India And Its Health Burdenmentioning
confidence: 99%